The Role of Physical Activity in Reducing Inflammation: Implications for Preventive Medicine - Kmieć, Justyna Weronika; Kulej, Piotr; Woźniak, Justyna; Biesiada, Wiktor; Chernysh, Anna-Mariia; Dusińska, Aleksandra; Waszczyński, Jakub; Fuczyło, Kamila; Stankevič, Karolina (Quality in Sport, 2025)
Physical activity is an accessible and free, modifiable factor which influences our health and wellbeing. Increased physical activity (PA) and exercise are associated with reduced chronic disease risk. The prevalence of physical inactivity is constantly increasing. Physical inactivity is associated with the development of various chronic diseases including cancer, cardiovascular, metabolic and neurodegenerative diseases [1]. All countries should adopt policies focused on encouraging people to move at all stages of life. Understanding the links that exist between PA and inflammation can bring new vision on common chronic disease. There is no doubt it would favorably impact global society on the economic as well as productivity side. This review highlights anti-inflammatory effects of PA and exercise training in selected, frequent illnesses our time. Purpose of the work: The purpose of this review is to explore and synthesize current scientific evidence on the anti-inflammatory effects of PA and exercise training, focusing on their impact on the prevention and management of chronic diseases. Materials and Methods: We conducted a literature search on the MEDLINE database in October 2024, utilizing keywords including 'physical activity', 'inflammation', ‘exercise’ and 'exerkine' to identify pertinent documents. The inclusion criterion was that the article addresses the following issues: the relationship between PA and inflammation in chronic diseases, the biochemical mechanisms linking physical activity to anti-inflammatory effects. Non-English language, or without full-text available articles, and publications not addressing the issues described in the inclusion criteria and were excluded from the analysis.